SEJARAH EKONOMI ISLAM MASA KONTEMPORER - Santoso, Sugeng (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
This literature study is explore and compare of Islamic scholarâs thought in contemporary era: Baqr al Sadr, Muhammad Abdul Mannan, Muhammad Nejatullah Siddiqi, Sayyed Haidar Naqf, Taqiyyuddin An Nabhanni, and Monzer Kahf. Islamic scholars are divided into three categories; frstly, an expert in the Islamic law (fqh) that is conducted in a legalistic and normative; secondly, more daring modernist group in their interpretation of Islamic teachings in order to answer the issues facing society today; thirdly practitioners or Muslim economists educational background in the West. They combine both Islamic law and economic approach that is integrated to be Islamic economy. In fact, the construction of an Islamic economy system capable of delivering on welfare and social justice must be built on the basis of faith (akidah) and described in great detail the concepts of ownership, the role of the state, and distribution, including production and consumption. Even distribution of income in society into the most important thing in the construction of an Islamic economy system, but all of it was related to other elements. Therefore, the construction of an Islamic economy system can not stand alone, but must be integrated and connected with other elements.Keywords: Islamic economy, Islamic scholars, Contemporary